Evaluation of expelled soybean meal in starter diets - C G Mills; K G Friesen; Robert D Goodband; Michael D Tokach; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1991)
Forty-eight weanling pigs (6.9 lb initial wt) were used in a 28-d growth study to determine the feeding value of expelled soybean meal (43% CP) as compared to conventionally extracted soybean meal (48.5% CP). Pigs were fed one of two dietary treatments containing either expelled soybean meal or conventional soybean meal. Both diets contained milo and 10% dried whey and were formulated to be slightly lysine deficient (.95%) to determine any potential differences in amino acid availabilities between the two soybean meals. From d 0 to 14, pigs fed conventional soybean meal had higher average daily gain (ADG) and average daily feed intake (ADFI) and were more efficient (F/G; 26.2%, 11.3%, and 21.6%, respectively) than pigs fed expelled soybean meal. Similar trends were noted for the overall experiment (d 0 to 28)} with pigs fed conventionally extracted meal having greater ADG (16.1 %) and ADFI (8.8%) and better F/G (6.2 %) than pigs fed the expelled soybean meal. Both soybean meal products were analyzed for percentage fat; the expelled meal contained 6.2% and conventional meal contained .83 %. The added fat in the expeller meal did not improve F/G compared to the conventional soybean meal. Protein solubility in both expelled and conventionally extracted soybean meal was greater than 70%, thus neither meal was overprocessed. However, trypsin inhibitor activity was higher in the expelled soybean meal (3.4 mg/g) as compared to the conventional soybean meal (.5 mg/g). This difference may be responsible for the poorer ADG, ADFI, and F/G found when feeding the expelled soybean meal. Based on this research, expelled soybean meal has approximately 84% the feeding value of conventionally extracted soybean meal when formulated on a lysine basis.; Swine Day, Manhattan, KS, November 21. 1991
Keywords: Swine day; 1991; Kansas Agricultural Experiment Station contribution; no. 92-193-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 641; Swine; Starter; Performance; SBM; Process; Soybean